Book review: Sevil, Acar. 2017: The Curse of Natural Resources: A Development Analysis in a Comparative Context. (April 2019) - Villar, Paul Fenton
Sevil, Acar. 2017: The Curse of Natural Resources: A Development Analysis in a Comparative Context . New York, NY: Palgrave Macmillan. 244 pp. RRP £88.00 (Hardback), ISBN 978-1-137-58722-0.